Deep frontal and periventricular age related white matter changes but not basal ganglia and infratentorial hyperintensities are associated with falls: cross sectional results from the LADIS study. Issue 6 (9th February 2009) - Blahak, C; Baezner, H; Pantoni, L; Poggesi, A; Chabriat, H; Erkinjuntti, T; Fazekas, F; Ferro, J M; Langhorne, P; O'Brien, J; Visser, M C; Wahlund, L-O; et al.
Abstract : Background: Global age related white matter changes (ARWMC) are associated with progressive gait disturbances and falls, hypothesised to result from interruptions of cortico-subcortical circuits controlling balance, posture and locomotion. Methods: The location of ARWMC in a large cohort of elderly non-disabled individuals with reported falls was analysed, using the cross sectional data of the Leukoaraiosis and Disability (LADIS) study. Detailed anatomical distributions of ARWMC assessed by MRI studies were analysed with respect to falls and balance performance. Results: The severity of global ARWMC was significantly associated with a history of falls in the year prior to study inclusion (22.2% in the mild, 31.6% in the moderate and 37.3% in the severe ARWMC group according to the Fazekas scale; p = 0.002). Analysing the anatomical distribution of ARWMC, using the semiquantitative Scheltens scale, in multivariate analysis, periventricular (p = 0.006) and frontal deep (p = 0.033) ARWMC were independently associated with falls. Furthermore, logistic regression identified frontal deep (p = 0.003) ARWMC, but not basal ganglia and infratentorial hyperintensities, as significantly associated with balance disturbances. Conclusion: The association of frontal and periventricular ARWMC with falls supports the hypothesis that interruption of frontal subcortical motor circuits lead to balance disturbances and hence to an increased risk for falls in ARWMC.